Pelatihan Pengembangan Trichokompos Sebagai Inovasi Kewirausahaan dan Pemberdayaan Petani Milenial di Kabupaten Enrekang - Suharman Suharman; Nurhapisah Nurhapisah; Rista Astari Rusdin; Jusran Jusran; Reski Reski; Dewi Sartika (Jurnal Pengabdian UNDIKMA, 2022)
This community service program aims to increase the knowledge and skills of farmer groups through entrepreneurship-based Trichokompos development training. This service uses training method with target partners, namely Tunas Muda Kreatif Farmer Group, Curioo Village, Enrekang Regency, South Sulawesi Province. The instrument for evaluating this activity was a questionnaire and analyzed descriptively. The result of this service activity is an increase in the knowledge of farmer groups about entrepreneurship and they are able to produce Trichoderma sp and Trichokompos in greater numbers. In addition, farmer groups have been able to market Trichokompos products so that they get economic benefits and can have an impact on plant growth which can be seen from the performance of pepper plants which are different from before, which is carried out through experiments and demplot